Implementation of the Pancasila Student Profile Strengthening Project in SMA Kategori Mandiri at Bandar Lampung City, Indonesia - Yanzi, Hermi; Faisal, Emil El; Mentari, Ana; Rohman, Rohman; Seftriyana, Elisa (FKIP Universitas Lampung, 2022)
nalysis of the Implementation of the Pancasila Student Profile Strengthening Project (P5) in Junior High School Category of the Independent Changed Bandar Lampung City. Objective: The research aims to analyze the implementation of the Pancasila Student Profile Strengthening Project, category of Independent School Sharing. Methods: This study used a qualitative approach with a case study method, intended to identify objective and in-depth conditions of course the focus of the study. Findings: The results of this study illustrate the implementation of the curriculum. There is a misconception about the implementation of the Pancasila Student Profile Strengthening Project program in schools with a changing self-category, one of which is that self-category schools change, one of which is project activities fixated on existing teaching material activities, not adjusting school environmental conditions, project activities are still dominant this is not the process of internalizing Pancasila Student Profile values, but rather the process of internalizing Pancasila Student Profile values. Conclusion: Schools need to carry out evaluation and retraining related to the philosophy of implementing the Pancasila Student Profile Project.Keywords: Pancasila student profile strengthening project, charactersDOI: http://dx.doi.org/10.23960/jpp.v12.i3.202232